Pest insects in cassava plantations intercrop with different plants at Gunungkidul, Yogyakarta, Indonesia - Nurkomar, Ihsan; Dina Wahyu Trisnawati; Siti Nur Aisyah (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
Cassava is one of the most widely cultivated food crops. One of the cassava production center is located in Gunungkidul, Yogyakarta, Indonesia. Due to the limited information on pests associated with cassava, especially in Gunungkidul, this study was conducted to investigate the diversity of insect pests in cassava plantations in this location. The study was carried out in three locations i.e., Bedoyo, Karangasem, and Kenteng Village. Insect sampling was performed in three areas within each location as many as four times. Each area consisted of five sampling plots. In total, there were 9 areas and 45 sampling plots. Insect sampling was conducted using yellow pan traps and sweeping net. A total of 23500 individuals of insect pests collected in 8 orders, 47 families, and 95 species. The most common orders were Hemiptera (31 species), Coleoptera (25 species), Diptera (13 species), Lepidoptera (11 species), and Orthoptera (10 species). Other species such as Isoptera (1 species), Thysanoptera (2 species), and non-insects Acari (2 species). The diversity of insect pests and the number of individuals (abundance) of insect pests differ between locations. Nonmetric multidimensional scale analysis shows that there are differences in the composition of insect pest species between locations. The highest diversity of pest species was found in Bedoyo Village. The most common species was also observed in Bedoyo compared to other location caused by the high population of whitefly (Bemisia tabaci) and mealybug (Ferrisia virgata, Paracoccus marginatus, and Pseudococcus jackbeardsleyi).